Development of a Medical Information System with Data Storage and Intelligent Image Analysis - D. A. Yakimov; N. V. Vygovskaya; I. V. Drozdov (Цифровая трансформация)
The relevance of the development of medical information systems for otolaryngology with artificial intelligence is substantiated, the process of developing an effective storage of medical data, taking into account their heterogeneity, is described. The task of storing medical data is complicated by the legal significance, large volume, heterogeneous and complex structure of information. A test version of an automated workstation for medical information systems for storing and processing medical research results has been developed. In the process of creating a new medical information system, the tasks of the first stage were solved: the structure and organization of the medical data warehouse were developed; procedures have been implemented for downloading, storing and viewing the results of medical research in DICOM format, identifying each patient to provide all related research results; criteria for dividing images into categories (TRG, RCT) were developed and implemented. The new system provides support for various types of search and access to the server from any computer in the corporate network of the otolaryngology department. Conditions have been prepared for the implementation of the second stage – integration of an automated workstation of medical information systems into the existing technological process in a medical institution and detection of pathology using an artificial neural network.